A case report of ovotesticular disorder of sex development (OT‐DSD) in a baboon (Papio spp.) and a brief review of the non‐human primate literature. Issue 3 (5th March 2018) - Perminov, Ekaterina; Mangosing, Sara; Confer, Alexandra; Gonzalez, Olga; Crawford, Jason R.; Schlabritz‐Loutsevitch, Natalia; Kumar, Shyamesh; Dick, Edward
Abstract: Disorders of sexual development are rare in non‐human primates. We report a case of true hermaphroditism in a 19‐year‐old, nulliparous, female baboon ( Papio spp.). At necropsy, the animal was obese with adequate muscle mass and hydration. Reproductive organs appeared normal with the exception of 2 firm nodular structures in the myometrium (1‐1.5 cm diameter) and a thickened, dark endocervical mucosa. Histologically, both gonads were ovotestes and contained discrete areas of ovarian and testicular tissue. There were follicles in various stages of development surrounded by ovarian stroma. Other areas contained hypoplastic seminiferous tubules lined by Sertoli cells, but lacked germ cells and spermatozoa. The uterine lesions were consistent with adenomyosis and cystic endometrial hyperplasia. Cervical lesions were consistent with atypical glandular hyperplasia and squamous metaplasia with dysplasia. We report the first case of ovotesticular disorder of sexual development (OT‐DSD), or true hermaphroditism in a baboon.